VERB ELLIPSIS IN CHARLES DICKENSâ€™S NOVEL: â€œBLEAK HOUSEâ€ ELLIPSIS VERBA DALAM NOVEL CHARLES DICKENS: â€œBLEAK HOUSEâ€ - Aryanti, Susan (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2018)
This research entitled â€œVerb Ellipsis in Charles Dickensâ€™s Novel: Bleak Houseâ€ discusses about the existence of verb ellipsis in the clause of the novel. The research uses theory from Nunan in his book entitled â€œIntroducing Discourse Analysisâ€ (1993). This research also uses theory from McShane in his book entitled â€œA Theory of Ellipsisâ€ (2005). In addition, this research uses descriptive method to analyze the data based on the discussion. The data are taken from the novel Bleak House by Charles Dickens because it has many words that are omitted although the reader can still understand. Based on the analysis, the data can be indicated as verba ellipsis. It also includes the type of verba ellipsis, which is gapping. The data can be indicated as gapping because the verb can be omitted in the second part of the clause since it contains the same verb, such as verb position in the first and second clause. In other words, gapping is an ellipsis process that makes unseen verb. Additionally, this research is made to describe the role of verba ellipsis in the clause or in the conversation of the novel. Moreover, it also completes the previous research to discuss ellipsis especially about verb ellipsis.